5a2 + 6ab=a(5a+6b)
b(6a-8) if you are factoring
2a x 3b = 6ab
To factorize the expression 4ab - 6ab, you first need to identify the common factor between the two terms, which is 2ab. You can then factor out this common factor to rewrite the expression as 2ab(2 - 3). Therefore, the fully factorized form of 4ab - 6ab is 2ab(2 - 3) or simply -2ab.
6ab inches
2a x 3b = 6ab
5a2 + 6ab=a(5a+6b)
6ab-3b factorize = 3
0.3333
3a2b is the simplest formImproved Answer:-3a x 2b = 6ab when simplified
12ab
6ab
24ab
To simplify the expression 6a^2 - 6ab + 7a^2, first combine like terms. Combine the terms with the same variable (a) raised to the same power. This results in 13a^2 - 6ab as the simplified expression. Remember to keep the terms in standard form with the variable term first, followed by any constant terms.
12ab
3a
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b